Strategies for the integration of culture to the acquisition of a foreign language - Ling Nieto, María del Rocío (2022)
The objective of this research is to determine intercultural elements' implementation´s impact to enhance integral education and improve foreign languages learning experience, specifically, English. The research was virtually performed in synchronous sessions due to Covid-19 during the second term in 2021 at Programa Institucional de Idiomas para el Trabajo (PIT). PIT is the academic unit responsible for languages teaching in different technical majors at Universidad Técnica Nacional (UTN). The research included a total of 87 participants; whose conversational level ranked from A1 to B1. The proposal was carried out through an action-research methodology focused on qualitative and quantitative analysis. The study was carried for a total of fourteen weeks, six of those weeks were selected to implement several strategies. English was used in contextualized scenarios that encouraged knowledge reflection of intercultural aspects of Costa Rica and English-speaking countries. The results showed positive opinions regarding the impact of integrating intercultural elements to increase the interest in participation and second language acquisition.